Secure Data Transform in Encrypted Image Using Steganography Technique - Malatesh, M; Anitha, G; Venkatesh, Ujjini (International Journal of Computer Sciences and Engineering, 2015)
The mean of the paper is to apply computer vision technique to transmit secret messages from sender to receiver. Cryptography and steganography are the two techniques to transform secret messages. In this paper steganography technique is used. Steganography is the hiding and transmitting secret data to the authorised user. One of the hiding techniques utilised here is LSB manipulation. System generate 3 keys using AES 128 bit algorithm based on these keys ,sender and receiver can encrypt and decrypt secret messages respectively. MySQL server, net beans IDE tool is used to obtain results.